Human parvovirus B19 infection in HIV-positive patients Infecção por parvovirus humano B19 em pacientes HIV-positivos - Fábio S. Aguiar; Daniella P. Lopes; Anna Ricordi Bazin; Sérgio Setúbal; Bernard J. Cohen; Jussara P. Nascimento (Revista da Sociedade Brasileira de Medicina Tropical, 2001)
Parvovirus B19 infects predominantly erythroid cells, leading to transient inhibition of erythropoiesis. Immunocompromised patients may be unable to produce neutralizing antibodies and may develop severe chronic anemia. Epidemiological studies done on Niterói population showed that B19 infection occurs periodically in late spring and summer. We report a study from 55 HIV infected patients attending an infectious diseases outpatient clinic in this city during a 5-month period in which B19 circulation was well documented. All patients were under anti-retroviral therapy. No anti-B19 IgM was found, but a high prevalence of IgG anti-B19 (91%) was observed. In six patients, B19 DNA was found by dot-blot hybridization techniques, but this was not confirmed by PCR. None of these 6 patients manifested anemia and only one had CD4 cell count below 200 x 10(7)/L. We conclude that persistent infection causing anemia is an infrequent finding in our HIV positive patients under drug therapy. O parvovírus B19 infecta predominantemente células eritróides, causando inibição transitória da eritropoiese. Pacientes imunocomprometidos podem ser incapazes de produzir anticorpos neutralizantes, evoluindo com grave anemia crônica. Estudos epidemiológicos da população de Niterói mostraram que a infecção ocorre periodicamente no final da primavera e no verão. Descrevem-se 55 pacientes infectados pelo HIV atendidos num ambulatório de doenças infecciosas nesta cidade num período de cinco meses, no qual a circulação do parvovírus B19 foi documentada. Todos os pacientes estavam sob terapia anti-retroviral. Não se encontrou IgM anti-B19, mas notou-se uma prevalência alta de IgG anti-B19 (91%). Em seis pacientes verificou-se a presença de DNA do B19 por hibridização em dot-blot, o que não se confirmou por PCR. Nenhum destes seis pacientes tinha anemia, e apenas um tinha células CD4 abaixo de 200 x 10(7)/L. Conclui-se que infecção persistente causando anemia é um achado infreqüente em nossos pacientes HIV positivos sob terapia medicamentosa.